Ultrasonic phase array and eddy current methods for diagnostics of flaws in friction stir welds; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Rubtsov V. E. Valery Evgenjevich; Tarasov S. Yu. Sergei Yulievich; Kolubaev Е. А. Evgeny Aleksandrovich; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen